Pengaruh Diskon Produk, Promosi Dan Variasi Produk Terhadap Keputusan Pembelian Di Aplikasi Efood : Studi Kasus Pada Generasi Z Di Kelurahan Teluk Pucung - Rizka Rahmah Nabiilah; Hadita Hadita; Neng Siti Komariah (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine and prove whether the effect of product discounts, promotions and product variations suimultan and partial has a significant effect on purchasing decisions in the eFOOD application. In this study using quantitative research methods and in obtaining this research sample the author used purposive sampling method. The number of samples used in this study was 102 respondents where the focus of these respondents was eFOOD application users in generation Z in Teluk Pucung Village. The results of the research that have been carried out there are variables that influence each other and there are also variables that do not influence, such as the following explanation: 1. The product discount variable partially does not affect the purchase decision because the original resulting from the partial test calculation shows a t-count value of 1.812 and a t-table of 1.984 so that it can be concluded that 1.812 < 1.989 and obtained a value significant 0.073 > 0.05. 2. The product promotion variable partially affects the purchase decision with the results of partial test calculations showing a t-count value of 5.046 and a t-table of 1.984 so that it can be concluded that 5.046 > 1.989 and obtained a significant value of 0.000 < 0.05. 3. In the variable product variation partially affects the decision with the test results and data analysis, partial test calculation results are obtained which show a t-count value of 2.724 and t-table of 1.984 so that it can be concluded that 2.724 > 1.989 and obtained a significant value of 0.008 < 0.05.